Claim Types in Canada’s Refugee Determination System: An Empirical Snapshot (2013–2021) - Rehaag, Sean (Refuge: Canada’s Journal on Refugees, 2024)
This article overviews outcomes in different types of refugee claims in Canada. It critiques standard legal research methodologies in the refugee law field due to skews in publication practices. To address these skews, the article employs empirical quantitative research methods using administrative tribunal data and computational methods. It provides a snapshot of refugee claim numbers, countries of origin, claim categories, and outcomes. The article then underscores the benefits of supplementing doctrinal legal research with empirical quantitative research methods, outlines barriers to the adoption of such methods, and offers guidance and tools to assist other researchers in overcoming those barriers.